Antioxidant activity, phytochemical screening and TLC profiling of Elaeis guineensis / Zahirah Aminuddin - Aminuddin, Zahirah (Faculty of Plantation and Agrotechnology, 2018)
Oil palm or Elaeis guineensis is a leading tropical vegetable oil worldwide. Many countries have been cultivated Elaeis guineensis includes Malaysia, Thailand and Indonesia. From the previous study, it showed that the leaves and fruit of oil palm rich in phenolic compound which have antioxidant properties. Therefore, the study was aimed to determine the antioxidant activity and potent chemical constituent in oil palm tree namely roots and it waste product such as empty fruit bunches, kernel shell, pressed cake and chipped trunk. Phytochemical screening has been done by identifying the presences of alkaloid, flavonoid, tannin, saponin and terpenoid. TLC profiling were also carried out in order to find the best solvent system to isolate pure compound in the crude extract. Solvents used were hexane, ethyl acetate, chloroform and methanol. The result of DPPH scavenging activity indicates roots and kernel shell have IC50. Phytochemical screening also showed the presence of alkaloid in most of the sample. Meanwhile, TLC profiling give the best solvent system of hexane and ethyl acetate with ratio of 2 to 8 (2:8). Thus, waste product of oil palm industry may contain valuable compounds for the study of their pharmacological potential in future.